Wavelength conversion member, its manufacturing method, and light emitting device
The wavelength conversion member, featuring a phosphor layer bound by light-transmitting ceramic and a protective layer formed by atomic layer deposition, addresses issues of heat resistance and light emitting properties, ensuring high luminous efficiency and compatibility with high output light sources.
Patent Information
- Application Number
- JP2021053166
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-26
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-03-26
AI Technical Summary
Conventional wavelength conversion members face issues with heat resistance and light emitting properties, particularly when used with high-energy light sources, due to the degradation of phosphor particles and the formation of pores and unevenness in the phosphor layer.
A wavelength conversion member is developed with a phosphor layer formed by light-transmitting ceramic that binds phosphor particles together, and a protective layer with an average thickness of 10 nm to 500 nm, formed using the atomic layer deposition method, to enhance heat resistance and light scattering suppression.
The proposed solution effectively protects the phosphor layer from external factors, reduces light scattering, and prevents heat storage, thereby maintaining high luminous efficiency and accommodating high output light emitting devices.
Smart Images

Figure 0007671609000003 
Figure 0007671609000004 
Figure 0007671609000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a wavelength conversion member, a manufacturing method thereof, and a light emitting device. [Background technology]
[0002] There is a known light-emitting device that uses a wavelength conversion material that converts light emitted from a light source such as a light-emitting diode (LED) or laser diode (LD) into light of a different wavelength using a phosphor layer and emits it. In recent years, the number of applications using LDs as light sources, which are highly energy efficient and can be easily made smaller and have higher output, is increasing.
[0003] In the conventional structure in which phosphors are dispersed in resins such as epoxy and silicone as the phosphor layer, the resin burns and discolors as the light source becomes more powerful, and the characteristics deteriorate quickly. In response to this issue, wavelength conversion members made only of inorganic materials using inorganic binders instead of resins have been devised, and the issue of heat resistance has been resolved even when used as a high-energy light source.
[0004] In addition, various phosphors are used for the phosphor particles used in the phosphor layer depending on the required color tone and characteristics. Some of the phosphor particles used in the phosphor layer are materials whose characteristics are easily deteriorated by external factors, and there is a demand for technology to suppress the deterioration of the phosphor particle characteristics.
[0005] Patent Document 1 discloses a wavelength conversion member in which a coating layer is further formed on the surface of a phosphor layer formed on a base material. The coating layer improves the surface hardness and prevents phosphor particles from falling off due to cracks that originate from pores contained inside the phosphor layer.
[0006] Patent Document 2 discloses a color-converting inorganic molded body in which a phosphor layer including granular phosphor particles and a coating layer is formed on a substrate. The phosphor layer is formed by coating the surfaces of the phosphor particles with a coating layer made of ceramics and bonding the phosphor particles together. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2018-165757 A [Patent Document 2] JP 2013-203822 A Summary of the Invention [Problem to be solved by the invention]
[0008] In the wavelength conversion member described in Patent Document 1, a coating layer made of Si-Bi-B type low-melting point glass is formed on the surface of the phosphor layer by screen printing to a thickness of 7 μm or more and 25 μm or less.
[0009] This improves the surface hardness and prevents the phosphor particles from falling off, but the thick coating layer makes the phosphor layer more likely to accumulate heat, which may result in a decrease in light-emitting properties. The surface of the phosphor layer has irregularities due to differences in the particle diameters of the phosphor particles, but when the film is formed by screen printing, the irregularities on the surface of the phosphor layer cannot be filled efficiently, and air holes are formed between the coating layer and the phosphor layer. This may result in a decrease in adhesion between the coating layer and the phosphor, or unwanted light scattering on the surface of the phosphor layer.
[0010] In the color-converting inorganic molded body described in Patent Document 2, a thin and dense coating layer is formed by atomic layer deposition (ALD) on a particle layer that is an aggregate of phosphor particles formed by electrodeposition. The coating layer also functions as a so-called binder that bonds the phosphor particles together. However, in the phosphor layer of Patent Document 2, since the phosphor particles exist as aggregates, there is a risk that the interval between adjacent particles becomes too narrow. This may make it difficult to convert the light source light into a desired color. For example, when attempting to obtain white by transmitting a part of the blue light source light and converting the remaining light source light into yellow, green, or red by a wavelength conversion member, there is a risk that the transmission of the blue light, which is the light source light, may be suppressed too much.
[0011] The present invention has been made in view of the above circumstances, and has an object to provide a wavelength conversion member that maintains resistance to external factors and has excellent light emission characteristics, a manufacturing method thereof, and a light emitting device. [Means for solving the problem]
[0012] (1) In order to achieve the above object, a wavelength conversion member of the present invention is a wavelength conversion member comprising: a base material; a phosphor layer provided on the base material, the phosphor layer including phosphor particles and a translucent ceramic that bonds the phosphor particles to each other and to the base material and the phosphor particles; and a protective layer provided on a surface of the phosphor layer, the protective layer having an average thickness of 10 nm or more and 500 nm or less, and the thickness of the protective layer being approximately uniform.
[0013] In this way, a protective layer is provided on the surface of the phosphor layer, and the protective layer has an average thickness of 10 nm or more and 500 nm or less, and the thickness of the protective layer is approximately uniform. Therefore, the phosphor layer is protected from external factors, light scattering in the protective layer is less likely to occur, and heat accumulation in the phosphor layer is less likely to occur, thereby suppressing a decrease in luminous efficiency.
[0014] (2) In the wavelength conversion member of the present invention, the phosphor layer is characterized in that, when a line parallel to a main surface of the substrate facing the phosphor layer is drawn in an SEM image of any cross section perpendicular to the substrate, the phosphor particle abundance is 50% or more and 80% or less, and the maximum interparticle distance of the phosphor particles is 100 μm or less.
[0015] In this way, since the abundance rate of the phosphor particles is 50% or more and 80% or less, a certain amount of light source light (excitation light) irradiated from the light emitting element is allowed to pass through, and for example, a wavelength conversion member irradiated with light source light having a blue light source transmits blue light while combining the light converted by the phosphor particles with the light source light to obtain emitted white light with good color balance. In addition, since the maximum interparticle distance of the phosphor particles is 100 μm or less, it is possible to suppress excessive transmission of the light source light through a part of the phosphor layer.
[0016] (3) In the wavelength conversion member of the present invention, the protective layer is made of any one of aluminum oxide, silicon oxide, and zinc oxide. The protective layer in the present invention needs to be light-transmitting, and since these materials are light-transmitting, any of them can be suitably used as the protective layer.
[0017] (4) Furthermore, the light emitting device of the present invention is a light emitting device, characterized in that it comprises a light emitting element that emits light of a specific range of wavelengths, and a wavelength conversion member described in any one of (1) to (3) above.
[0018] In this way, the average thickness of the protective layer provided on the surface of the phosphor layer of the wavelength conversion member is 10 nm to 500 nm, and the thickness of the protective layer is approximately uniform, so that the light emitting device can suppress heat generation and a decrease in luminous efficiency of the wavelength conversion member and can accommodate high output of the light emitting element. Such a light emitting device can be used for laser lighting, laser projectors, etc.
[0019] (5) Furthermore, a method for producing a wavelength conversion member of the present invention is a method for producing a wavelength conversion member, comprising the steps of: preparing a wavelength conversion member precursor including a base material; and a phosphor layer provided on the base material and formed of phosphor particles and a translucent ceramic that bonds the phosphor particles to each other and to the base material and the phosphor particles; and forming a protective layer having a thickness of 10 nm to 500 nm on the phosphor layer of the wavelength conversion member precursor by atomic layer deposition (ALD).
[0020] In the manufacturing method of the present invention, a protective layer is formed on the phosphor layer of the wavelength conversion member precursor by atomic layer deposition (ALD) to a thickness of 10 nm to 500 nm, and a wavelength conversion member having a protective layer with an average thickness of 10 nm to 500 nm and a substantially uniform thickness can be manufactured. As a result, a thin protective layer with a substantially uniform thickness and less defects such as pinholes can be formed, and the phosphor layer can be protected from external factors. In addition, the protective layer is less likely to scatter light and the phosphor layer is less likely to accumulate heat, so that a decrease in luminous efficiency is suppressed. In addition, the thickness of the protective layer is more preferably 50 nm to 300 nm in consideration of these effects and productivity. Effect of the Invention
[0021] According to the present invention, it is possible to construct a wavelength conversion member and a light emitting device using the same, which can protect the phosphor layer from external factors while preventing light scattering in the protective layer and heat accumulation in the phosphor layer, thereby suppressing a decrease in light emitting efficiency. [Brief description of the drawings]
[0022] [Figure 1] FIG. 2 is a cross-sectional view showing an example of a cross-sectional structure of a wavelength conversion member according to an embodiment of the present invention. [Diagram 2] 10A and 10B are cross-sectional views showing modified examples of the cross-sectional structure of the wavelength conversion member according to the embodiment of the present invention. [Diagram 3] 1A and 1B are conceptual diagrams each showing a part of an example of a light emitting device according to an embodiment of the present invention. [Figure 4] 4 is a flowchart illustrating an example of a method for producing a wavelength conversion member according to an embodiment of the present invention. [Diagram 5] 4 is a flowchart showing an example of detailed steps of a protective layer forming step according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Next, an embodiment of the present invention will be described with reference to the drawings. In order to facilitate understanding of the description, the same reference numerals are used for the same components in each drawing, and duplicated descriptions will be omitted. In the configuration diagrams, the size of each component is conceptually shown, and does not necessarily represent the actual dimensional ratio.
[0024] [Configuration of wavelength conversion material] 1 is a cross-sectional view showing an example of the cross-sectional structure of a wavelength conversion member 10 according to this embodiment. In the wavelength conversion member 10 of this embodiment, a phosphor layer 14 is formed on a base material 12, and a protective layer 19 is formed on the surface of the phosphor layer 14. The wavelength conversion member 10 transmits or reflects incident light irradiated from a light source, and is excited by the incident light to generate light of different wavelengths. For example, the wavelength conversion member 10 transmits or reflects incident blue light, and emits converted light of green, red, or yellow converted by the phosphor layer 14, and can convert the converted light and the incident light together, or use only the converted light, into light of various colors.
[0025] The shape of the base material 12 may be any shape that is applicable to the light emitting device 40, and may be a variety of shapes such as a circle, a rectangle, an ellipse, a polygon, etc. Also, as shown in Fig. 2, the base material 12 may be concave with an opening at the top, and the phosphor layer 14 and the protective layer 19 may be provided in the concave portion.
[0026] The material of the base material 12 is appropriately selected according to the intended use. When used for transmitting the excitation light from the light emitting element, inorganic materials such as sapphire and glass can be used. It is particularly preferable to use sapphire, which has high thermal conductivity, and by suppressing heat accumulation in the phosphor layer 14, the deterioration of the characteristics of the phosphor particles 16 due to temperature rise can be suppressed. When used for reflecting the excitation light from the light emitting element, aluminum, iron, copper, etc., or ceramics can be used. In particular, it is preferable to use aluminum, which has high thermal conductivity and high reflectance in the entire visible light range, and by suppressing heat accumulation in the phosphor layer 14, the deterioration of the characteristics of the phosphor particles 16 due to temperature rise can be suppressed. In addition, a reflective layer may be formed by providing a light reflective material such as silver by plating or vapor deposition on the main surface 13, which is the surface of the base material 12 on the phosphor layer 14 side, or a reflection-enhancing film such as TiO2 may be formed.
[0027] The phosphor layer 14 is provided as a film on the substrate 12, and is formed of phosphor particles 16 and translucent ceramics 18. The translucent ceramics 18 bonds the phosphor particles 16 together and also bonds the phosphor particles 16 to the substrate 12. This allows efficient heat dissipation when irradiated with high-energy-density light, as it is bonded to the substrate 12, which functions as a heat dissipation material, and can suppress temperature quenching of the phosphor. The thickness of the phosphor layer 14 is preferably 15 μm or more and 300 μm or less, and more preferably 50 μm or more and 200 μm or less.
[0028] The phosphor layer 14 may contain inorganic particles in addition to the phosphor particles 16 and the light-transmitting ceramics 18. When inorganic particles are mixed, inorganic particles that meet various purposes can be mixed. For example, the purpose may be to adjust the viscosity of the phosphor paste, to adjust the density of the phosphor particles in the phosphor paste, to scatter light in the phosphor layer, to improve the thermal conductivity of the phosphor layer, to reduce voids in the phosphor layer, etc. The average particle size of the inorganic particles is preferably equal to or smaller than the average particle size of the phosphor particles contained in the phosphor layer 14.
[0029] Furthermore, when a line parallel to the main surface 13 of the substrate 12 on the phosphor layer 14 side is drawn in an SEM image of any cross section perpendicular to the substrate 12, the abundance ratio of the phosphor particles 16 is preferably 50% to 80%. Furthermore, it is preferable that the maximum interparticle distance of the phosphor particles 16 is 100 μm or less. The abundance ratio of the phosphor particles 16 tends to increase by reducing the amount of binder added or by adjusting the mixing time to be shorter, while the maximum interparticle distance can be suppressed to 100 μm or less by appropriately dispersing the phosphor particles 16 in the phosphor layer 14 by adjusting the mixing time.
[0030] A method for confirming the abundance rate of phosphor particles 16 and the maximum interparticle distance by SEM images will be described in detail below. First, an SEM image of a cross section in a direction perpendicular to the planar direction of the substrate 12 is obtained at, for example, 1000 times magnification. Next, image analysis such as binarization is performed on the obtained SEM image, and a range of the image recognized as the phosphor layer 14 is determined from the image. Then, a plurality of (for example, three) imaginary lines parallel to the main surface 13 of the substrate 12 are drawn at positions that equally divide the phosphor layer 14 in the thickness direction, and the abundance rate of phosphor particles 16 and the maximum interparticle distance are calculated for each imaginary line. In addition, the average value of the abundance rate of phosphor particles 16 can be obtained from the average value. The abundance rate of phosphor particles 16 is calculated from the proportion of phosphor particles 16 present on the imaginary line. That is, the ratio of the length of phosphor particles 16 crossing the imaginary line to the length of the imaginary line is expressed in percentage (%). The maximum interparticle distance is the maximum value of the distances on a virtual line between adjacent phosphor particles 16. Note that the images used to calculate the average abundance rate of phosphor particles 16 and the maximum interparticle distance are obtained by acquiring cross-sectional images (e.g., three or more) of multiple locations in phosphor layer 14 so as to obtain overall values.
[0031] For example, yttrium aluminum garnet phosphors (YAG phosphors) and lutetium aluminum garnet phosphors (LAG phosphors) can be used for the phosphor particles 16. In addition, the phosphor particles 16 can be selected from the following materials depending on the design of the color to be emitted. For example, BaMgAl10 O 17 :Eu, ZnS:Ag,Cl, blue phosphors such as BaAl2S4:Eu or CaMgSi2O6:Eu, Zn2SiO4:Mn, (Y,Gd)BO3:Tb, ZnS:Cu,Al, (M1)2SiO4:Eu, (M1)(M2)2S:Eu, (M3)3Al5O 12 Examples of the phosphors include yellow or green phosphors such as (M1)SiO:Eu, (M1)SiO:Eu, (M1)S:Eu, and (Ba,Sr,Mg)SiO:Eu, and red phosphors such as (M1)SiO:Eu, (M1)S:Eu, and red phosphors such as (Y,Gd)BO:Eu, Y2OS:Eu, (M1)Si5N8:Eu, (M1)AlSiN3:Eu, and YPVO4:Eu. In the above chemical formula, M1 includes at least one of the group consisting of Ba, Ca, Sr, and Mg, M2 includes at least one of Ga and Al, and M3 includes at least one of the group consisting of Y, Gd, Lu, and Te. The above phosphor particles 16 are examples, and the phosphor particles 16 used in the wavelength conversion member 10 are not necessarily limited to the above.
[0032] The average particle diameter of the phosphor particles 16 is preferably 5 μm or more and 50 μm or less, and more preferably 7 μm or more and 30 μm or less. When it is 5 μm or more, the luminous intensity of the converted light is increased, and thus the luminous intensity of the wavelength conversion member 10 is increased. When it is 50 μm or less, the thickness of the phosphor layer 14 can be easily adjusted, and the risk of the phosphor particles 16 falling off can be reduced. In addition, the temperature of each phosphor particle 16 can be kept low, and thermal quenching can be suppressed. In this specification, the average particle diameter is the median diameter (D50). The average particle diameter can be measured using a dry measurement or wet measurement with a laser diffraction / scattering type particle size distribution measuring device.
[0033] The translucent ceramics 18 are formed by hydrolysis or oxidation of an inorganic binder, and are made of an inorganic material having translucency. The translucent ceramics 18 are made of, for example, silica (SiO2) or aluminum phosphate. In addition, since the translucent ceramics 18 are translucent, they can transmit light from a light source (incident light) and converted light. Since the translucent ceramics 18 are made of an inorganic material, they have improved heat resistance and are less likely to deteriorate even in applications where high-energy light such as LD is irradiated.
[0034] As the inorganic binder, for example, ethyl silicate, an aqueous solution of aluminum phosphate, or the like can be used.
[0035] A translucent material is one that has the property that when light in the visible light wavelength range (λ = 380 to 780 nm) is irradiated perpendicularly to a 0.5 mm target material, the radiant flux of the light that exits from the opposite side exceeds 80% of the incident light.
[0036] The protective layer 19 is a layer provided for the purpose of suppressing the deterioration of the luminous properties of the phosphor particles 16 caused by the influence of external factors, and is formed so as to protect the phosphor layer 14 from external factors and suppress the influence on the luminous efficiency of the phosphor particles 16. The luminous properties refer to the luminous intensity of the phosphor particles 16 and the property of emitting a desired color. The protective layer 19 is only required to protect the phosphor layer 14 from external factors, and is formed so as to cover at least the surface of the phosphor layer 14. Note that, as shown in FIG. 2, when the base material 12 is concave and the phosphor layer 14 is contained in the concave portion of the base material 12, only the upper surface may be covered. The protective layer 19 may also be formed on the base material 12 on which the phosphor layer 14 is not formed.
[0037] The protective layer 19 is made of an inorganic material having translucency, and is preferably made of any one of aluminum oxide, silicon oxide, and zinc oxide. Any of these materials have translucency and can be suitably used as the protective layer 19. This allows the layer to transmit absorbed light and converted light without being altered even when irradiated with high-energy light such as that from a laser diode.
[0038] The protective layer 19 is formed by deposition using the ALD method. The ALD method is a deposition method in which a film is deposited one layer at a time on the surface of an object at the atomic level, and is capable of depositing a smooth and very thin film. The protective layer 19 deposited using the ALD method has excellent film adhesion, is a dense film with uniform thickness, and can suppress the occurrence of defects such as pinholes. That is, the protective layer 19 deposited using the ALD method is formed so that the vertical distance from the surface of the deposition target to the outer surface of the protective layer 19 is approximately uniform. Therefore, the protective layer 19 formed on the phosphor layer 14 having the unevenness due to the phosphor particles 16 is formed so as to follow the shape of the surface of the phosphor layer 14.
[0039] The surface roughness Ra of the protective layer 19 is preferably 0.1 μm or more and 2.0 μm or less. In the case of a reflective wavelength conversion member, since the surface roughness Ra is 0.1 μm or more, the regular reflection component on the surface of the phosphor layer 14 is suppressed, and color unevenness and spots of the light irradiated from the wavelength conversion member 10 are unlikely to occur. On the other hand, since it is 2.0 μm or less, it is possible to suppress uneven reflection caused by the surface roughness, and it is possible to suppress the occurrence of color unevenness. Furthermore, in the case of a transmissive wavelength conversion member, since the surface roughness Ra is 0.1 μm or more, it is possible to suppress the internal reflection of light within the base material 12. On the other hand, since it is 2.0 μm or less, it is possible to maintain the light transmittance of the base material 12 high over the entire visible light range.
[0040] The raw materials for the protective layer 19 formed by the ALD method include organometallic materials, metal halide compounds, and the like. As described above, the protective layer 19 is preferably formed from any one of aluminum oxide, silicon oxide, and zinc oxide, and the raw materials for the protective layer 19 are selected according to the material constituting the protective layer 19. For example, when forming the protective layer 19 made of aluminum oxide, TMA (trimethylaluminum), water, and the like are used as raw materials.
[0041] The average thickness of the protective layer 19 is 10 nm or more and 500 nm or less. Because the average thickness of the protective layer 19 is 10 nm or more, it is a sufficient thickness to protect the phosphor layer 14. Because it is 500 nm or less, a decrease in the emission intensity can be suppressed.
[0042] The average thickness of the protective layer 19 can also be measured by analyzing an SEM image. The thickness of the protective layer 19 in the SEM image analysis is measured by obtaining an SEM image of a cross section in a direction perpendicular to the planar direction of the main surface 13 of the substrate 12, for example, at 1000 times magnification. Next, image analysis such as binarization is performed on the obtained SEM image, and the range of the image recognized as the protective layer 19, the range of the image recognized as the phosphor layer 14, and the range of the image recognized as the substrate 12 are determined. Next, straight lines are drawn perpendicular to the main surface 13 of the substrate 12 at equal intervals (for example, 20 μm), and the intersections between the straight lines and the surface of the phosphor layer 14 are obtained. Then, a straight line is further drawn perpendicular to the surface of the phosphor layer 14 at the intersections, and the intersections between the straight lines and the surface of the protective layer 19 are obtained, and the distance between the two intersections (the intersections of the surfaces of the phosphor layer 14 and the protective layer 19) is taken as the thickness value of the protective layer 19 at that position. In this way, a plurality of thicknesses of the protective layer 19 at a certain position are calculated, and the average thickness of the protective layer 19 can be calculated from the average value. Note that the images used to calculate the average thickness of the protective layer 19 are cross-sectional images (e.g., three or more) of a plurality of positions in the protective layer 19 so as to obtain an overall average value.
[0043] The difference between the maximum and minimum values of the thickness of the protective layer 19 and the average thickness of the protective layer 19 is preferably 20% or less, more preferably 10% or less, of the average thickness of the protective layer 19. In this way, the protective layer 19 is formed so that the difference between the maximum and minimum values of the thickness of the protective layer 19 and the average thickness is 20% or less of the average thickness, respectively, so that the variation in the thickness of the protective layer 19 is suppressed, and light scattering in the protective layer 19 is less likely to occur. The maximum and minimum values of the thickness of the protective layer 19 are the maximum and minimum values of the multiple thickness values of each cross section used when calculating the thickness of the protective layer 19. Note that the thickness of the protective layer 19 is approximately uniform when the difference between the maximum and minimum values of the thickness of the protective layer 19 and the average thickness is 20% or less. The protective layer 19 formed by the ALD method satisfies this condition.
[0044] [Configuration of the light-emitting device] 3(a) and (b) are schematic diagrams showing a transmissive and reflective light emitting device of the present invention, respectively. The light emitting device 40 includes a light source 50 and a wavelength conversion member 10. The light source 50 is a light emitting element that generates light source light in a specific range of wavelengths, and may be, for example, an LED or an LD. Since the wavelength conversion member 10 can efficiently convert wavelengths even with high power, it is preferable that the light source 50 is an LD.
[0045] [Method of manufacturing wavelength conversion member] An example of a method for producing a wavelength conversion member will be described. Fig. 4 is a flow chart showing a method for producing a wavelength conversion member of the present invention. The method for producing a wavelength conversion member includes steps of preparing a wavelength conversion member precursor having a base material 12 and a phosphor layer 14 (steps S1 to S4), and a step of forming a protective layer 19 on phosphor layer 14 of the wavelength conversion member precursor (step S5). The steps of preparing the wavelength conversion member precursor (steps S1 to S4) will be described below in order.
[0046] First, the raw material is processed to prepare the base material 12 formed into a predetermined shape (step S1). Apart from the base material 12, phosphor particles 16 and an inorganic binder are mixed to prepare a phosphor paste (step S2). To prepare the phosphor paste, first, phosphor particles having a predetermined average particle size are prepared. Various phosphor particles 16 can be used depending on the design of the wavelength conversion member 10. Two or more types may be used. Next, the prepared phosphor particles 16 are weighed, dispersed in a solvent, and mixed with an inorganic binder to prepare a phosphor paste for printing. A ball mill or propeller stirring can be used for mixing. In the case of a ball mill, the mixing time is preferably 3 minutes or more and 30 minutes or less. In the case of propeller stirring, the mixing time is preferably 5 minutes or more and 120 minutes or less. This can reduce the variation in the thickness of the phosphor layer. As the solvent, a high boiling point solvent such as α-terpineol, butanol, isophorone, or glycerin can be used.
[0047] Next, a phosphor paste is applied to the surface of the base material 12 prepared in the base material preparation step (step S1) to form a paste layer (step S3). The phosphor paste can be applied by screen printing, spraying, drawing with a dispenser, or inkjet printing. Screen printing is preferable because it can stably form a paste layer of uniform thickness. The thickness of the paste layer is adjusted so that it has a predetermined thickness after heat treatment. The paste layer is preferably formed to fit the shape of the base material 12.
[0048] The applied phosphor paste is then heat-treated at a temperature of 300°C or less to form a phosphor layer (step S4). The heat treatment temperature is preferably 150°C or more and 300°C or less, and the heat treatment time is preferably 0.5 hours or more and 2.0 hours or less. The temperature rise rate is preferably 50°C / h or more and 200°C / h or less. A drying step may be performed before the heat treatment. The drying temperature is preferably 100°C or more and 150°C or less, and the drying time is preferably 20 minutes or more and 60 minutes or less.
[0049] Next, a protective layer is formed on the surface of the wavelength conversion member precursor produced through the heat treatment process (step S5). The protective layer 19 is formed by atomic layer deposition (ALD) so as to have a thickness of 10 nm to 500 nm.
[0050] The formation of the protective layer 19 will be described in more detail with reference to Fig. 5. Fig. 5 is a flow chart showing detailed steps of the protective layer forming step (step S5) in the present invention. The following describes the case where the raw material gas is TMA (trimethylaluminum), the reactive gas is H2O (water), and an aluminum oxide film is formed as the protective layer 19.
[0051] First, the wavelength conversion member precursor is placed in a deposition chamber and heated to 100° C. to 400° C. (step S5-1). Next, vaporized TMA is introduced into the chamber as a raw material gas and adsorbed onto the surface of phosphor layer 14 (step S5-2).
[0052] When only one layer of the source gas is adsorbed on the surface of the phosphor layer 14, the unadsorbed source gas is exhausted from the film formation chamber (step S5-3). The unadsorbed source gas is exhausted by introducing an inert gas such as helium or argon into the film formation chamber as a purge gas.
[0053] Next, vaporized water vapor is introduced into the film formation chamber as a reactive gas, and is reacted with the TMA adsorbed on the phosphor layer 14 (step S5-4). The TMA reacts with the water vapor to form an aluminum oxide film and also produces methane gas as a by-product.
[0054] When the source gas adsorbed on the surface of the phosphor layer 14 has sufficiently reacted with the reactive gas, the unreacted reactive gas and by-product gas are exhausted from the deposition chamber (step S5-5). The exhaust method may be the same as that for exhausting the source gas.
[0055] Through the above steps, one layer of the protective layer 19 is formed. In the protective layer forming process in this embodiment, the basic cycle is the raw material gas introduction step (step S5-2) to the exhaust step (step S5-5), which are repeated until the protective layer 19 reaches a thickness of 10 nm to 500 nm. Here, the thickness of the protective layer 19 formed in one cycle from the material of the protective layer 19 is calculated, and the number of cycles required for the desired thickness is calculated. After the exhaust step (step S5-5) is completed, it is determined whether the current number of cycles is equal to or greater than the calculated predetermined number (step S5-6). If the number of cycles is less than the predetermined number (No in step S5-6), the process returns to the raw material gas introduction step (step S5-5) and the protective film forming process is repeated. On the other hand, if the number of cycles is equal to or greater than the predetermined number (Yes in step S5-6), the protective film forming process is terminated.
[0056] In the ALD method, energy such as heat, plasma, light, voltage, etc. is applied to promote the reaction between the source gas and the reactive gas. For example, any ALD method may be used, including a thermal ALD method in which a film-forming body is heated, a method in which plasma is directly applied during the reaction between the source gas and the reactive gas, and a plasma ALD method in which plasma is used outside the reaction chamber to introduce activated reactive groups into the reaction chamber.
[0057] [Examples and Comparative Examples] (Preparation of wavelength conversion material) (Examples 1-1 to 1-5)
[0058] As the substrate 12, a disk-shaped substrate made of sapphire having a diameter of φ30 mm and a thickness of t1.0 mm was prepared.
[0059] For the phosphor layer, a nitride phosphor ((Sr,Ca)AlSiN3:Eu) with an average particle size of 15 μm, α-terpineol as a solvent, and ethyl silicate as an inorganic binder were weighed and mixed for 30 minutes with a propeller stirrer to produce a phosphor paste. The obtained raw material paste was applied to a substrate by screen printing so that the average thickness of the layer after heat treatment would be 100 μm, and the substrate after application was dried at 100°C for 20 minutes, and then heated to 150°C at 150°C / h in a non-oxidizing atmosphere using an electric furnace, and heat-treated for 60 minutes to produce a wavelength conversion member precursor of Example 1.
[0060] Next, protective layer 19 was formed on each wavelength conversion member precursor by ALD. At this time, the raw material gas was TMA (trimethylaluminum), the reactive gas was H2O (water), and the purge gas was N2, and each was supplied to the film formation chamber. The processing pressure was 10 Pa or more and 50 Pa or less. The temperature during film formation was 200°C.
[0061] Under the above conditions, an aluminum oxide film was formed as protective layer 19 in one cycle at a time, to produce the wavelength conversion members of Examples 1-1 to 1-5. The film formation rate was about 0.1 nm / cycle. A predetermined number of cycles of the protective layer formation step were performed to form an aluminum oxide film so that protective layer 19 had a thickness shown in Table 1 below.
[0062] In addition, after the high temperature and high humidity environment exposure test, the wavelength conversion member of Example 1-1 was cut and analyzed with an SEM image. As a result, the abundance ratio of phosphor particles in the phosphor layer was 70%, and the maximum interparticle distance was 30 μm.
[0063] Comparative Example 1 A wavelength conversion member of Comparative Example 1 was produced in the same manner as in Example 1, except that an aluminum oxide film having a thickness of 1 μm was formed as protective layer 19 by plasma CVD.
[0064] Comparative Example 2 The wavelength conversion member of Comparative Example 2 was produced in the same manner as Example 1, except that a slurry was prepared by dispersing aluminum oxide microparticles with an average particle diameter of 20 nm in an alcohol-based solvent, and the slurry was spray-coated onto the phosphor particles to a thickness of 100 nm.
[0065] Comparative Example 3 A wavelength conversion member of Comparative Example 3 was produced in the same manner as in Example 1, except that the protective layer 19 was not formed.
[0066] [Evaluation of wavelength conversion materials] (High temperature and humidity environment exposure test) The wavelength conversion member obtained above was irradiated with blue LD light having a wavelength of 465 nm and an output of 2 W. Then, the emission intensity was measured using a laser power meter, and the emission intensity measured at this time was defined as the emission intensity at time 0.
[0067] Next, the wavelength conversion member was placed in a sealed container (constant temperature and humidity chamber) in an environment of 85°C and 85% relative humidity and left to stand. At this time, the wavelength conversion member was prevented from coming into direct contact with water. Then, the emission intensity was measured every certain time, and the emission intensity measured at 0 hours in Comparative Example 3 was taken as 100%, and the time when the emission intensity of each wavelength conversion member became 90% or less was measured.
[0068] Table 1 below shows the luminescence intensity of each sample at each time, with the luminescence intensity at time 0 in Comparative Example 3 taken as 100%. [Table 1]
[0069] As shown in Table 1, in all of the tests of Examples 1-1 to 1-5, it took more than 1000 hours for the emission intensity to drop to 90% or less. Since the initial emission intensity tended to decrease as the thickness of the protective layer increased, a range of 50 nm to 300 nm was more preferable in consideration of manufacturing time and cost. In contrast, in Comparative Examples 1 to 3, the emission intensity dropped to 90% or less in less than 500 hours. In Comparative Examples 1 and 2, there were areas where film formation was not possible and pinholes existed along the complex surface unevenness of the phosphor layer, and it is believed that the decrease in emission intensity over time occurred from these areas. In Comparative Example 1, which was thicker than the other examples, the initial emission intensity was the lowest. This confirmed that the wavelength conversion member of the present invention can suppress the decrease in emission intensity in a high-temperature, high-humidity environment. In addition, since nitride phosphors are particularly susceptible to external factors among phosphor particles, the wavelength conversion member of the present invention can suppress the decrease in emission intensity in a high-temperature, high-humidity environment even when other phosphor particles 16 are used.
[0070] (Production of wavelength conversion material) Example 2 Except for using YAG phosphor as the phosphor particles, the wavelength conversion member of Example 2 was produced at the same level as Example 1. Furthermore, after the light emission characteristic test, the wavelength conversion member was cut and analyzed with SEM images, and as a result, the abundance ratio of the phosphor particles in the phosphor layer was 70%, and the maximum interparticle distance was 30 μm.
[0071] Example 3 The wavelength conversion member of Example 3 was produced in the same manner as Example 2, except that the mixing time, phosphor particle diameter, binder amount, etc. were adjusted to change the abundance ratio of phosphor particles in the phosphor layer to 50% and the maximum interparticle distance to 70 μm.
[0072] Example 4 The wavelength conversion member of Example 4 was produced in the same manner as Example 2, except that the mixing time, phosphor particle diameter, binder amount, etc. were adjusted to change the abundance ratio of phosphor particles in the phosphor layer to 80% and the maximum interparticle distance to 25 μm.
[0073] Example 5 Except for using LuAG phosphor as the phosphor particles, the wavelength conversion member of Example 5 was produced at the same level as Example 2. In addition, as a result of analyzing SEM images, the abundance ratio of the phosphor particles in the phosphor layer was 70%, and the maximum interparticle distance was 35 μm.
[0074] Comparative Example 4 The wavelength conversion member of Comparative Example 4 was produced in the same manner as in Example 2, except that the mixing time, phosphor particle diameter, binder amount, etc. were adjusted to change the abundance ratio of phosphor particles in the phosphor layer to 40% and the maximum interparticle distance to 120 μm.
[0075] Comparative Example 5 The wavelength conversion member of Comparative Example 5 was produced in the same manner as in Example 2, except that the mixing time, phosphor particle diameter, binder amount, etc. were adjusted to change the abundance ratio of phosphor particles in the phosphor layer to 85% and the maximum interparticle distance to 20 μm.
[0076] [Evaluation of wavelength conversion materials] (Light Emitting Property Test) Blue LD light with a wavelength of 465 nm was used as laser light with a laser input of 2 W and irradiated onto wavelength conversion member 10. The chromaticity of the light transmitted to the opposite side to the irradiated surface was measured using a spectroradiometer (CL-500A manufactured by Konica Minolta).
[0077] Chromaticity is a numerical representation of the color properties hue, saturation, and brightness, excluding brightness. In this specification, chromaticity is represented using a pair of numbers (x, y) corresponding to the xy chromaticity diagram of the CIE-XYZ color system, an international display method established by the International Commission on Illumination (CIE) in 1931. In the xy chromaticity diagram, the larger the x-axis number, the greater the proportion of "redness," and the smaller the number, the greater the proportion of "blueness." On the y-axis, the larger the number, the greater the proportion of "greenness," and the smaller the number, the greater the proportion of "blueness."
[0078] To confirm the luminescence characteristics, the color deviation (duv) from the blackbody locus on the CIE chromaticity diagram was calculated for the measured chromaticity, and those with a color deviation within a range of ±0.02 were evaluated as having good luminescence characteristics. [Table 2]
[0079] As shown in Table 2, in Examples 2 to 4, the color deviation was within the range of ±0.02. In contrast, in Comparative Example 4, the color deviation was outside the range of ±0.02. This is believed to be because too much blue light was transmitted. In Comparative Example 5, the color deviation was outside the range of ±0.02. This is believed to be because the transmission of blue light was too restricted, preventing sufficient blue light from transmitting.
[0080] From the above results, it was confirmed that the wavelength conversion member of the present invention protects the phosphor layer from external factors, and is unlikely to cause light scattering in the protective layer, and is unlikely to cause heat accumulation in the phosphor layer, thereby suppressing a decrease in luminous intensity. In addition, since a certain amount of light source light (excitation light) irradiated from a light emitting element is allowed to pass through, it was confirmed that, for example, a wavelength conversion member irradiated with light source light having a blue light source transmits blue light, while combining the converted light converted by the phosphor particles with the light source light to obtain a white light emission light with good color balance. In addition, it was confirmed that the manufacturing method of the wavelength conversion member of the present invention can manufacture the above-mentioned wavelength conversion member.
[0081] The present invention is not limited to the above-described embodiment, and it goes without saying that various modifications and equivalents are included within the spirit and scope of the present invention. In addition, the structure, shape, number, position, size, etc. of the components shown in each drawing are for convenience of explanation and may be changed as appropriate. [Explanation of symbols]
[0082] 10 Wavelength conversion material 12 Base material 13 Main surface 14 Phosphor layer 16 Phosphor particles 18 Translucent ceramics 19 Protective layer 40 Light emitting device 50 light source
Claims
1. A wavelength conversion member, A substrate; a phosphor layer provided on the base material, the phosphor layer including phosphor particles and a light-transmitting ceramic that bonds the phosphor particles to each other and to the base material and the phosphor particles; a protective layer provided on a surface of the phosphor layer, the translucent ceramic is formed from an inorganic binder; the protective layer is provided at least on a surface of the translucent ceramic, The protective layer has an average thickness of 10 nm or more and 500 nm or less, The thickness of the protective layer is substantially uniform, The phosphor layer is a wavelength conversion member characterized in that, when a line parallel to the main surface of the substrate on the phosphor layer side is drawn in an SEM image of any cross section perpendicular to the substrate, the maximum interparticle distance of the phosphor particles is 25 μm or more and 100 μm or less.
2. 2. The wavelength conversion member according to claim 1, characterized in that, when a line parallel to a main surface of the substrate on the phosphor layer side is drawn in an SEM image of any cross section perpendicular to the substrate, the phosphor layer has an abundance rate of the phosphor particles of 50% or more and 80% or less.
3. 3. The wavelength conversion member according to claim 1, wherein the protective layer is made of any one of aluminum oxide, silicon oxide, and zinc oxide.
4. A light emitting device, comprising: A light emitting element that emits light in a specific range of wavelengths; A light emitting device comprising: the wavelength conversion member according to claim 1 .
5. A method for producing a wavelength conversion member, comprising: preparing a wavelength conversion member precursor including a base material, and a phosphor layer provided on the base material and formed of phosphor particles and a translucent ceramic that bonds the phosphor particles to each other and to the base material and the phosphor particles; forming a protective layer having a thickness of 10 nm to 500 nm on the phosphor layer of the wavelength conversion member precursor by atomic layer deposition (ALD); the translucent ceramic is formed from an inorganic binder; the protective layer is provided at least on a surface of the translucent ceramic, The method for manufacturing a wavelength conversion member, wherein the phosphor layer of the wavelength conversion member has a maximum interparticle distance of 25 μm or more and 100 μm or less when a line parallel to the main surface of the substrate on the phosphor layer side is drawn in an SEM image of any cross section perpendicular to the substrate.
Citation Information
Patent Citations
Inorganic molded article for color conversion and method for producing the molded article, and light-emitting device
JP2013203822A
Wavelength conversion member and manufacturing method thereof, and light-emitting device
JP2016100485A
Wavelength conversion member and manufacturing method thereof
JP2018165757A
Method for manufacturing molded body, molded body, and light-emitting device
JP2022052552A